2016
DOI: 10.1371/journal.pone.0162153
|View full text |Cite
|
Sign up to set email alerts
|

A Regulated Double-Negative Feedback Decodes the Temporal Gradient of Input Stimulation in a Cell Signaling Network

Abstract: Revealing the hidden mechanism of how cells sense and react to environmental signals has been a central question in cell biology. We focused on the rate of increase of stimulation, or temporal gradient, known to cause different responses of cells. We have investigated all possible three-node enzymatic networks and identified a network motif that robustly generates a transient or sustained response by acute or gradual stimulation, respectively. We also found that a regulated double-negative feedback within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The concordance between the model simulations and the experimental data indicates that the behaviour results from the network topology and connections and not from specific parameters in the model. Various network motifs that elicit different responses to static and dynamic inputs have been described previously 2 , 4 , 27 . For instance, Park et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concordance between the model simulations and the experimental data indicates that the behaviour results from the network topology and connections and not from specific parameters in the model. Various network motifs that elicit different responses to static and dynamic inputs have been described previously 2 , 4 , 27 . For instance, Park et al .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Park et al . (2016) found that a 3-node network motif with regulated double-negative feedback could give a transient response upon a static input, but a sustained response upon a dynamic gradient input 27 . Johnson et al .…”
Section: Resultsmentioning
confidence: 99%
“…The ODEs of the network model were constructed mainly based on Michaelis–Menten kinetics as follows:dfalse[normalEGFRafalse]italicdt=k1false[normalEGFfalse]·[EGFRi]false/Knormalm11+[EGFRi]false/Knormalm1+[Cetuximab]false/Knormali1knormald1[EGFRa]dfalse[normalKRASafalse]italicdt=k2normala[EGFRa]+k2normalb[normalGNB5]·false[normalKRASifalse]Knormalm2+[KRASi]knormald2[KRASa]dfalse[normalMEKafalse]italicdt=k3false[normalKRASafalse]·false[normalMEKifalse]Knormalm3+[MEKi]knormald3[MEKa]dfalse[normalERKafalse]italicdt=k4false[normalMEKafalse]·false[normalERKifalse]Knormalm4+[ERKi]knormald4[ERKa]…”
Section: Methodsmentioning
confidence: 99%
“…The ODEs of the network model were constructed mainly based on Michaelis-Menten kinetics [55] as follows:…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…[42] Another study observed that stimulating cultured neurons with different temporal gradients of brain-derived neurotrophic factor (BDNF) produced different cellular responses that resulted from interconnected positive and negative feedback loops. [43] By identifying such circuits within a larger complex network, systems biology can uncover the critical circuits to effectively target with new drugs, as well as the circuits that are involved in the responses to currently used drugs. Additionally, because systems biology reveals dynamic properties of networks, this approach can guide the kinetics of drug delivery.…”
Section: Network Dynamics and Drug Resistancementioning
confidence: 99%